FEATURES OF STRUCTURAL STRUCTURE AND RELATIONSHIPS OF BASALT FIBRES FOR APPLICATIONS (Neo Science Peer Reviewed Journal, 2023)
Continuous basalt fibres offer a unique combination of good mechanical and functional properties at an affordable price level. These properties can be useful in high-performance polymer matrix composites, where cost orientation and function integration become priority goals. In this work, a currently unsolved problem of basalt fibres related to high productivity is considered: the variation of the structural and mechanical properties of the fibre due to the inhomogeneity of the natural raw materials and the spinning process. Commercial basalt fibres from seven different manufacturers were studied for their fibre chemistry, diameter distribution, and occurrence of defects and crystallites. In the second stage, structure-property relationships of different scales were established with one fibre.